PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN CIPUTRA HOSPITAL TANGERANG - Hertina, Leni; Sabur, Ambuy (Journal of Business Education and Social, 2022)
Job training and career development have an important role to improve the performance of employees and improve quality human resources. The purpose of this study was to determine the effect of training and career development simultaneously and partially on the performance of Ciputra Hospital Tangerang Hospital employees. This research is a causal associative study where the population and sample of this study are employees at Ciputra Hospital Tangerang Hospital. The data analysis technique used is the normality test, F test, T test at the significant rate (confidence level) alpha 0.05. And the calculation process was carried out using the SPSS version 24 program. The hypothesis test showed that the results of the effect of job training on employee performance were 2,115 at a significant level of 0.038, the effect of career development on employee performance was 1,535 at a significant level of 0.130. Thus the hypothesis in this study shows that job training has a partial or positive effect on employee performance at Ciputra Hospital Tangerang Hospital while career development has no effect on employee performance